2015
DOI: 10.1179/1743289815y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Hemp fibre as alternative to glass fibre in sheet moulding compound. Part 2—impact properties

Abstract: This paper describes the results of falling weight impact tests on natural fibre reinforced polyester composites fabricated using a conventional sheet moulding compound (SMC) process. The influence of hemp fibre and CaCO 3 filler content on the penetration energy of hemp fibre reinforced sheet moulding compound (H-SMC) is reported and compared with glass fibre reinforced sheet moulding compound (G-SMC). To evaluate the influence of fibre/matrix interfacial adhesion on the impact behaviour of these H-SMCs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…For these authors, cohesive interfaces obtained by fibre treatments such as organosilanes only promoted increases in tensile stiffness and strength to the detriment of impact properties. In contrast, Patel et al [5] found that fibre surface treatments (silane and alkaline) promoting interfacial cohesion led to higher absorbed energy upon impact for hemp fibre reinforced polyester composites.…”
Section: Failure Surface Observations and Adhesion At The Fibre /Matrmentioning
confidence: 89%
See 4 more Smart Citations
“…For these authors, cohesive interfaces obtained by fibre treatments such as organosilanes only promoted increases in tensile stiffness and strength to the detriment of impact properties. In contrast, Patel et al [5] found that fibre surface treatments (silane and alkaline) promoting interfacial cohesion led to higher absorbed energy upon impact for hemp fibre reinforced polyester composites.…”
Section: Failure Surface Observations and Adhesion At The Fibre /Matrmentioning
confidence: 89%
“…Santulli et al [7][8][9] compared the impact behaviour of a flax / epoxy composite to a glass / epoxy composite with similar weight ratio reinforcement on a drop-weight impact test, and found a better impact resistance for the glass reinforced ones. Patel et al [5] and Scarponi et al [6] also showed that glass fibres reinforced polyester and epoxy composites have a slightly higher energy absorbed at breakage than hemp reinforced biocomposites. However at low fibre volume fraction (< 20 vol%), the difference was much smaller.…”
Section: Influence Of Impact Energymentioning
confidence: 99%
See 3 more Smart Citations